Mesenchymal Stromal Cell Immunology for Efficient and Safe Treatment of Osteoarthritis - Najar, Mehdi; Martel-Pelletier, Johanne; Pelletier, Jean-Pierre; Fahmi, Hassan (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem cell (MSC) therapy represents a promising approach for the treatment of osteoarthritis (OA). MSCs can be readily isolated from multiple sources and expanded ex vivo for possible clinical application. They possess a unique immunological profile and regulatory machinery that underline their therapeutic effects. They also have the capacity to sense the changes within the tissue environment to display the adequate response. Indeed, there is a close interaction between MSCs and the host cells. Accordingly, MSCs demonstrate encouraging results for a variety of diseases including OA. However, their effectiveness needs to be improved. In this review, we selected to discuss the importance of the immunological features of MSCs, including the type of transplantation and the immune and blood compatibility. It is important to consider MSC immune evasive rather than immune privileged. We also highlighted some of the actions/mechanisms that are displayed during tissue healing including the response of MSCs to injury signals, their interaction with the immune system, and the impact of their lifespan. Finally, we briefly summarized the results of clinical studies reporting on the application of MSCs for the treatment of OA. The research field of MSCs is inspiring and innovative but requires more knowledge about the immunobiological properties of these cells. A better understanding of these features will be key for developing a safe and efficient medicinal product for clinical use in OA.